2017
DOI: 10.1016/j.jfluidstructs.2017.06.003
|View full text |Cite
|
Sign up to set email alerts
|

A linear numerical model for analysing the hydroelastic response of a flexible electroactive wave energy converter

Abstract: In this paper, a linear mathematical and numerical model for analysing the dynamic response of a flexible electroactive wave energy converter is de- Finally, estimates are made for the energy performance of a possible prototype.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 12 publications
0
22
0
Order By: Relevance
“…In addition to tank testing, numerical models of the fluid structure interaction of the S3 device with the waves were set up, [ 159 ] dry‐run generation tests on the DEG modules along with reliability tests were conducted, [ 49 ] and layouts of scalable power electronics were identified (Section 3.3). [ 125 ] As an important conclusion, the authors suggested that the peak electric field to be cyclically applied on the DE material should be significantly lower than the BD value (they suggest a value of 60 kV mm −1 for silicones), for the system to reach a target lifetime on the order of 20 years (i.e., 45×106 cycles at the typical wave frequencies).…”
Section: Prototypes and Applicationsmentioning
confidence: 99%
“…In addition to tank testing, numerical models of the fluid structure interaction of the S3 device with the waves were set up, [ 159 ] dry‐run generation tests on the DEG modules along with reliability tests were conducted, [ 49 ] and layouts of scalable power electronics were identified (Section 3.3). [ 125 ] As an important conclusion, the authors suggested that the peak electric field to be cyclically applied on the DE material should be significantly lower than the BD value (they suggest a value of 60 kV mm −1 for silicones), for the system to reach a target lifetime on the order of 20 years (i.e., 45×106 cycles at the typical wave frequencies).…”
Section: Prototypes and Applicationsmentioning
confidence: 99%
“…In 2011, a 10 m long S3 WEC, equipped with 20 independent EAP generators, was tested in the Hydrodynamics and Ocean Engineering Tank of Ecole Centrale de Nantes. Numerical tools were developed to analyse the hydroelastic response of the device [90]. A recent mathematical model has also provided a means to calculate the maximal power absorption of the device based on the waves radiated in the far field.…”
Section: Bulge Wave Devicesmentioning
confidence: 99%
“…In addition to the test at sea, the numerical analytical governing equations for the standing wave tube type WEC were proposed by Babarit [77] in 2017. The governing equations for the behavior of the tube wall and flow inside and outside the tube were formulated.…”
Section: Wave Energymentioning
confidence: 99%